LESBIAN DALAM PERGULATAN GENDER DAN SEKSUALITAS DI SUDUT PASAR KARTIKA NIAGA, SURABAYA - Maria Nala Damayanti (Lakon : Jurnal Kajian Sastra dan Budaya, 2013)
The presence of women in same-sex sexual trend in Indonesia is considered unnatural. The actor suffered the injustice of the treatment. Condition that was not expected by the women does not make them desperate but appear to be driving their own to declare independence in the community generally. The research follows the lives of several lesbian experiences tells the respondent. Work and have their own income is the way to survive in the big city and at the same time strengthening their identity is still shrouded. A gender and sexual identity collide and the real personalities of women who never consciously chosen from the beginning. But the pressures and demands of life that makes them exist until now. Authors conducted a simple ethnographic approach was very useful in order to obtain accurate data. The research was conducted in Surabaya and done solely to open our eyes wider to the presence of women with different sexual orientation than most of us. It must be admitted some use of key terms in the analysis may be not too precise, perhaps even often confused as a synonym. Gender identity, sexual-biological, sexual orientation. The third term is still like a new food menu, let alone trying to comment on 'taste'. However, the authors sought to understand this discourse as closely as possible, be descriptive, with the hope of understanding themselves become better writers and story-telling flow, and thus contribute to the realm of gender and sexuality, no matter how small.